Acetalization of Carbonyl Compounds Catalyzed by Bismuth Triflate Under Solvent-Free Conditions - ALIYAN, HAMID; FAZAELI, RAZIEH; REZA MASSAH, AHMAD; REZA MOMENI, AHMAD; JAVAHERIAN NAGHASH, HAMID; MOEINIFARD, BEHZAD (Asian Journal of Chemistry, 2010)
Carbonyl compounds were converted to the corresponding 1,3-dioxolanes and 1,3-dioxanes with ethylene glycol and 1,3-propandiol in the presence of bismuth triflate under solvent-free conditions. In addition, high chemoselective protection of aldehydes in the presence of ketones has been achieved.